The Evaluation of the Impact of a Program of Online Training on the Level of Knowledge in Health Education and Research in Sub-Saharan African Environment. - Kelly, Tcheumagam; Djientcheu, Vincent de Paul (Journal of Health Informatics in Africa, 2020)
BACKGROUND: Many initiatives of e-learning have been developed in Sub-Saharan African countries, but no study has been carry up to evaluate the impact of this method of training in our context with his socio-economics particularities. The rational of this study is to evaluate the effect of an e-learning program using the Africa Build Portal on the level of the knowledge on final year medical students. METHODOLOGY: In this interventional study, the final year medical students of 2 universities in Cameroon (one private and one public) were summited to an on-line program of lectures. After a brief presentation of the lectures program the students were evaluated before (pre-test) and after (post-test) the training. A questioner was filled by each student to express the satisfaction and the obstacles encountered during the training. The training program was elaborated through South-South collaboration (Mali-Cameroon-Ghana) with a support of North (ITM-WHO). RESULTS: A total of 121 students over 129 were registered; 112 students (92%) followed the online lectures and underwent the whole online procedure (pretest, training, posttest and the questioner filling) were included. The mean age was 25.16 years (range from 22-33years). The sex ratio 1:1. The mean marks of student on pre-test was 43.32/100 compared to mean marks of post-test 69.69/100 (p = 0.0001E-21). The significant difference on pretest between the students who in addition followed the face to face presentation (83 students) and the others did not appear on the post- test. The main obstacles to e-learning were the poor bandwidth internet connection and the overload academic program with less free time. The module on EBM and the methodology of the research were more visited with a total of 12275273 minutes and a mean of 1301.29 min per page because of the direct impact on the ongoing redaction and defense of their thesis. CONCLUSION: Under certain conditions, e-learning is an effective method of training even in Sub-Saharan African countries. This is a good indicator to promote numeric libraries in that environment. The motivation of the learner is a key point to consider. The parameter to improve is the individual and institutional internet connectivity.